PEMETAAN DAERAH PENANGKAPAN IKAN PELAGIS KECIL UNTUK MENINGKATKAN HASIL TANGKAPAN NELAYAN DI PERAIRAN KOTA MAKASSAR - Asbar, Asbar; Ihsan, Ihsan (JURNAL PENGABDIAN MASYARAKAT KAUNIAH, 2022)
Community groups in Untia Village, Biringkanaiya Subdistrict, Makassar City are mostly fishermen whose targets are small pelagic fish such as kites, bloating, lemuru, selar and fishermen still tradisonla. This research aims to map small pelagic fishing grounds in the waters of Makassar City, while its use is as a fisherman information material to increase catches. The data collected is primarily and secondary data, which is analyzed using geographic information systems. The results of the analysis and discussion conducted showed that the prediction map of the potential fishing area of small pelagic fishing in the waters of Makassar City tends to move around and not permanent every time, in the western season is around Langkai and Lanjukkang to the southwest. Conventional methods or habits of experience carried out by his ancestors so that the development is slow and very fanatical with experience obtained for generations must be changed.